Deep cyclones in the southeast Gulf of Mexico - Safaie, Aryan; Donohue, Kathleen A.; Rowley, Clark D.; Thoppil, Prasad G.; Watts, D. Randolph (Frontiers in Marine Science, 2025)
In the Gulf of Mexico (GoM), as the warm Loop Current (LC) extends into the southeastern Gulf, strong deep eddies are energized through LC interaction with topography and baroclinic instability. A 6-year free-running numerical simulation using a regional configuration of the Navy Coastal Ocean Model (NCOM) shows the importance of deep cyclones to Loop Current Eddy (LCE) formation, particularly in the deep region south of 25°N, circumscribed by the Yucatán Strait to the south and the steep lateral sidewalls of the Campeche Bank and the Florida Shelf to the west and east, respectively. Four eddy shedding events from this simulation illustrate ways that deep cyclones develop and strengthen jointly from baroclinic development as well as from lower-layer stretching when the LC moves away from the channel sidewalls. In all cases, the deep cyclone plays a key role: one event depicts the classic baroclinic joint-development process; two events demonstrate the influence of the steep bathymetry along the Campeche Bank and Florida Shelf in restricting lateral propagation; the fourth event emphasizes the role of a deep cyclone in preventing reattachment of a detached eddy. As deep cyclones are important in determining LCE separation, we advocate for more observation and modeling attention on the dynamics of the deep southeast channel.